2016
DOI: 10.13188/2330-2178.1000028
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated with Substance Abuse and Anxiety on Immigrant and U.S. Born Latinos

Abstract: Latinos are exposed to adverse psychosocial factors that impact their health outcomes. Given the heterogeneity and rapid growth of this population, there is an urgent need to understand the mechanisms through which psychosocial factors impact substance abuse and anxiety between immigrant and U.S. born Latino adults. The present study employs a multi-group path analysis using Mplus 7.2 to examine generational differences in the paths between affiliation culture, years of formal education, contact with important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
(122 reference statements)
0
1
0
1
Order By: Relevance
“…, en su análisis de los modelos explicativos del consumo de drogas que sirven de base teórica para los programas de prevención, muestra cómo es necesario transitar de modelos donde predominan variables como la actitud, el control conductual percibido, las creencias y otras de franca naturaleza psicológica, a modelos integradores de variables del individuo y su entorno. Trabajos como el de López-Tamayo et al, que se anuncia como el estudio de factores psicosociales asociados con el consumo de sustancias, incluye los años de educación y la aculturación como factores de peso en su modelo(López-Tamayo et al, 2016). Esto sin contar la extensa literatura sobre la aplicación de los enfoques ecológicos al asunto de las drogas citada previamente.…”
unclassified
“…, en su análisis de los modelos explicativos del consumo de drogas que sirven de base teórica para los programas de prevención, muestra cómo es necesario transitar de modelos donde predominan variables como la actitud, el control conductual percibido, las creencias y otras de franca naturaleza psicológica, a modelos integradores de variables del individuo y su entorno. Trabajos como el de López-Tamayo et al, que se anuncia como el estudio de factores psicosociales asociados con el consumo de sustancias, incluye los años de educación y la aculturación como factores de peso en su modelo(López-Tamayo et al, 2016). Esto sin contar la extensa literatura sobre la aplicación de los enfoques ecológicos al asunto de las drogas citada previamente.…”
unclassified
“…The literature with respect to alcohol use treatment and acculturation is still emerging. However, one study found that lower levels of past 6-month alcohol use was negatively associated with acculturation (Lopez-Tamayo et al, 2016). Although the authors suggest that the scale can be used cross-culturally, it has been used most often with Latinx and Asian subgroups.…”
Section: Summary Of Review Findingsmentioning
confidence: 99%